2017
DOI: 10.1097/igc.0000000000001111
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism in Gynecological Malignancy

Abstract: Gynecological malignancy-associated VTE is associated with significant morbidity, contributing to a large number of life years lost. Although promising new therapies are emerging, a 2-pronged approach is required to simultaneously target cancer-specific management and predict early on those who are likely to be affected. In the meantime, clinicians should continue to combine current guidelines with a multidisciplinary team approach to ensure that these complex patients receive the best evidence-based and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 57 publications
(78 reference statements)
2
26
0
2
Order By: Relevance
“…Of these, lymphocele is one of the most common postoperative complications in that it leads to the occurrence of VTE by venous compression [54,55]. According to a review of the literature, VTE occurred after lymphadectomy at an estimated incidence of 0.8-25% [56][57][58]. This is also seen in our results.…”
Section: Discussionsupporting
confidence: 83%
“…Of these, lymphocele is one of the most common postoperative complications in that it leads to the occurrence of VTE by venous compression [54,55]. According to a review of the literature, VTE occurred after lymphadectomy at an estimated incidence of 0.8-25% [56][57][58]. This is also seen in our results.…”
Section: Discussionsupporting
confidence: 83%
“…It is understandable why regional fibrosis and post-therapy pelvic tissue ischemia account for the parietal dysfunction at the level of the ureteral wall and also for the venous or lymphatic walls, explaining complications such as DVT, bowel obstruction, hydronephrosis, or lymphedema, being directly proportional to the amount of aggression. [ 6 , 12 , 13 , 15 , 22 , 23 ] A study done by Kim et al [ 9 ] showed that a lower incidence of pelvic lymphocele can be seen if postoperative radiotherapy is not applied, suggesting a more cautious choice of adjuvant treatment. In only 1 study, performed by Achouri et al, [ 16 ] did adjuvant radiotherapy have a beneficial effect, by significantly reducing number of symptomatic pelvic lymphocele, but this study does not mention whether radiotherapy lowers the number of lymphocele altogether.…”
Section: Discussionmentioning
confidence: 99%
“…Thromboembolism is one of the most common complications of malignancy that can occur before or after the diagnosis of Unusual presentation of ovarian cancer cancer. 7 A hypercoagulable state can occur in patients with cancer due to interactions between monocyte/macrophages with malignant cells causing the release of tumor factors such as tumor necrosis factor and interleukins-1 and -6. 11 This leads to endothelial damage and sloughing of endothelial cells, which acts as a thrombogenic surface to activate intrinsic and extrinsic coagulation factors that convert prothrombin to thrombin to generate thrombi.…”
Section: Discussionmentioning
confidence: 99%
“…5 Cancers associated with a higher incidence of stroke are lung, pancreatic, and colorectal cancers. 3,6 VTE disease (pulmonary embolism [PE] and deep vein thrombosis [DVT]) are significantly associated with ovarian cancer 7 and adversely impact patient survival. [7][8][9][10] This case report outlines the discovery of occult ovarian cancer in a patient who exhibited acute cerebrovascular events with an incidental detection of patent foramen ovale (PFO).…”
mentioning
confidence: 99%